Network-based pharmacological examination of the potential effector mechanisms of Achyranthes bidentata on osteoarthritis treatment - Junfeng WANG; Xuefeng GUAN; Yongju YANG; Pengpeng LIU; Tao LIU; Qun WANG (Journal of Holistic Integrative Pharmacy)
[Abstract]: Objective: To employ network-based pharmacology techniques and methods for the examination of the active ingredients and potential effector mechanisms of Achyranthes bidentata in osteoarthritis treatment. Methods: The traditional Chinese medicine systems pharmacology (TCMSP) database was employed to screen for potential active components and associated target proteins of Achyranthes bidentata. Genecards and OMIM database were used to predict the effector targets of osteoarthritis. The UniProt database was used to search for the corresponding gene names. The compound osteoarthritis target network and protein–protein interaction (PPI) network for Achyranthes bidentata were built using Cytoscape and String software. The Bioconductor data package was used in R to evaluate GO biological function enrichment and KEGG pathway enrichment, and the effective components and targets of Achyranthes bidentata in the treatment of osteoarthritis were acquired. Results: Twenty key active components of Achyranthes bidentata were acquired by screening the TCMSP database. Overall, 106 targets are common effector targets of major chemical component-chemical component effector targets and osteoarthritis therapeutic target-osteoarthritis. 84 PPI core genes were acquired, and these participate in modulating 23 signaling pathways, such as the IL-17 signal pathway, TNF signal pathway, HIF-1 signal pathway, apoptosis, and other signaling pathways. Conclusion: Achyranthes bidentata treatment of osteoarthritis is a multi-component, multi-target, and multi-pathway complex process involving multiple targets associated to the coordinated modulation of signaling pathways.